2-Chloroethanol Induced Upregulation of Matrix Metalloproteinase-2 in Primary Cultured Rat Astrocytes Via MAPK Signal Pathways - Sun, Qi; Liao, Yingjun; Wang, Tong; Tang, Hongge; Wang, Gaoyang; Zhao, Fenghong; Jin, Yaping (Frontiers in Neuroscience, 2017)
This study was to explore the mechanisms underlying 1,2-dichloroethane (1,2-DCE) induced brain edema by focusing on alteration of matrix metalloproteinase-2 (MMP-2) in rat astrocytes induced by 2-chloroethanol (2-CE), an intermediate metabolite of 1,2-DCE in vivo. Protein and mRNA levels of MMP-2, and the phosphorylated protein levels of p38 MAPK (p-p38), extracellular signal regulated protein kinase (p-ERK1/2) and c-Jun N-terminal kinase (p-JNK1/2) in astrocytes were examined by immunostaining, western blot or real-time RT-PCR analysis. Findings from this study disclosed that protein levels of MMP-2 were upregulated by 2-CE in astrocytes. Meanwhile, protein levels of p-p38, p-ERK1/2 and p-JNK1/2 were also increased apparently in the cells treated with 2-CE. Moreover, pretreatment of astrocytes with SB202190 (inhibitor of p38 MAPK), U0126 (inhibitor of ERK1/2) or SP600125 (inhibitor of JNK1/2) could suppress the upregulated expression of p-p38, p-ERK1/2, and p-JNK1/2. In response to suppressed protein levels of p-p38 and p-JNK1/2, the protein levels of MMP-2 also decreased significantly, indicating that activation of MAPK signal pathways were involved in the mechanisms underlying 2-CE-induced upregulation of MMP-2 expression.